Comparison of numbers of interneurons in three thalamic nuclei of normal and epileptic rats - AKAKIN, DİLEK; ONAT, FİLİZ; ŞİRVANCI, SERAP (SPRINGER, 2014)
The inhibitory sources in the thalamic nuclei are local interneurons and neurons of the thalamic reticular nucleus. Studies of models of absence epilepsy have shown that the seizures are associated with an excess of inhibitory neurotransmission in the thalamus. In the present study, we used light-microscopic gamma-aminobutyric acid (GABA) immunocytochemistry to quantify the interneurons in the lateral geniculate (LGN), ventral posteromedial (VPM), and ventral posterolateral (VPL) thalamic nuclei, and compared the values from normal Wistar rats and genetic absence epilepsy rats from Strasbourg (GAERS). We found that in both Wistar rats and GAERS, the proportion of interneurons was significantly higher in the LGN than in the VPM and VPL. In the LGN of Wistar rats, 16.4% of the neurons were interneurons and in the GAERS, the value was 15.1%. In the VPM, the proportion of interneurons was 4.2% in Wistar and 14.9% in GAERS; in the VPL the values were 3.7% for Wistar and 11.1% for the GAERS. There was no significant difference between Wistar rats and the GAERS regarding the counts of interneurons in the LGN, whereas the VPM and VPL showed significantly higher counts in GAERS. Comparison of the mean areas of both relay cells and interneuronal profiles showed no significant differences between Wistar rats and GAERS. These findings show that in the VPL and the VPM there are relatively more GABAergic interneurons in GAERS than in Wistar rats. This may represent a compensatory response of the thalamocortical circuitry to the absence seizures or may be related to the production of absence seizures.
Keywords: immunohistochemistry; interneuron; relay neuron; thalamus; GABA; LATERAL GENICULATE-NUCLEUS; GABA-IMMUNOREACTIVE NEURONS; GENETIC ABSENCE EPILEPSY; RETICULAR NUCLEUS; WAVE DISCHARGES; GABAERGIC INTERNEURONS; SPONTANEOUS SPIKE; CAT; SEIZURES; LIGHT